The effects of music therapy in patients undergoing septorhinoplasty surgery under general anesthesia☆ - Gökçek,Erhan (2020)
Abstract Introduction Music has been used for several years as a relaxation method to reduce stress and anxiety. It is a painless, safe, inexpensive and practical nonpharmacologic therapeutic modality, widely used all over the world. Objectives We aimed to evaluate the effect of music therapy on intraoperative awareness, patient satisfaction, awakening pain and waking quality in patients undergoing elective septorhinoplasty under general anesthesia. Methods This randomized, controlled, prospective study was conducted with 120 patients undergoing septorhinoplasty within a 2 months period. The patients were randomly selected and divided into two groups: group music (music during surgery) and control group (without music during surgery). All patients underwent standard general anesthesia. Patients aged 18–70 years who would undergo a planned surgery under general anesthesia were included. Patients who had emergency surgery, hearing or cognitive impairment, were excluded from the study. Results A total of 120 patients were enrolled, and separated into two groups. There were no statistically significant differences between the groups in terms of demographic characteristics, anesthesia and surgery durations (p > 0.05). In the music group, sedation agitation scores were lower than those in the control group at the postoperative period (3.76 ± 1.64 vs. 5.11 ± 2.13; p < 0.001). In addition; in patients of the music group, the pain level (2.73 ± 1.28 vs. 3.61 ± 1.40) was lower (p < 0.001), requiring less analgesic drugs intake. Conclusion Music therapy, which is a nonpharmacologic intervention, is an effective method, without side effects, leading to positive effects in the awakening, hemodynamic parameters and analgesic requirements in the postoperative period. It is also effective in reducing the anxiety and intraoperative awareness episodes of surgical patients.